2015
DOI: 10.5194/acp-15-8361-2015
|View full text |Cite
|
Sign up to set email alerts
|

The impact of speciated VOCs on regional ozone increment derived from measurements at the UK EMEP supersites between 1999 and 2012

Abstract: Abstract. The impact of 27 volatile organic compounds (VOCs) on the regional O 3 increment was investigated using measurements made at the UK EMEP supersites Harwell (1999Harwell ( -2001Harwell ( and 2010Harwell ( -2012 and Auchencorth (2012). Ozone at these sites is representative of rural O 3 in southeast England and northern UK, respectively. The monthlydiurnal regional O 3 increment was defined as the difference between the regional and hemispheric background O 3 concentrations, respectively, derived from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…In areas heavily impacted by natural gas drilling, the ratios lie in the range of 0.82-0.89 (Gilman et al, 2013;Abeleira et al, 2017). Higher values are often reported for automobiles, in the range of 2.2-3.8 for vehicle emissions and 1.8-4.6 for fuel evaporation (McGaughey et al, 2004;Jobson et al, 2004;Russo et al, 2010;Wang et al, 2013), whereas ratios below unity were found for coal combustion (0.56-0.80) (Yan et al, 2017).…”
Section: Ratios Of Specific Compoundsmentioning
confidence: 96%
“…In areas heavily impacted by natural gas drilling, the ratios lie in the range of 0.82-0.89 (Gilman et al, 2013;Abeleira et al, 2017). Higher values are often reported for automobiles, in the range of 2.2-3.8 for vehicle emissions and 1.8-4.6 for fuel evaporation (McGaughey et al, 2004;Jobson et al, 2004;Russo et al, 2010;Wang et al, 2013), whereas ratios below unity were found for coal combustion (0.56-0.80) (Yan et al, 2017).…”
Section: Ratios Of Specific Compoundsmentioning
confidence: 96%
“…Figure 1 (Malley et al, 2015(Malley et al, , 2016Walker et al, 2019). Instruments at the Harwell site were relocated to Chilbolton Observatory in 2016, providing the opportunity to assess the satellite data at sites with distinct agricultural activity and anthropogenic influence (Walker et al, 2019).…”
Section: Space-based and Surface Air Quality Observationsmentioning
confidence: 99%
“…There are no direct reliable measurements of HCHO in the UK and measurements of NMVOCs are limited to a few sites that only measure light ( C9) hydrocarbons. Figure 1 shows locations of EMEP supersites in Harwell, England, south of Oxford (51.57° N, 1.32° W), Chilbolton Observatory, England, 40 miles south of Harwell (51.15° N, 1.44° W) and Auchencorth Moss, Scotland, south of Edinburgh (55.79° N, 3.24° W) (Malley et al, 2015;Walker et al, 2019). Instruments at the Harwell site were relocated to Chilbolton Observatory in 2016, providing the opportunity to assess the satellite data at sites with distinct agricultural activity and anthropogenic influence (Walker et al, 2019).…”
Section: Space-based and Surface Air Quality Observationsmentioning
confidence: 99%